Measurement uncertainty analysis of single-use flow sensors - Ludolph, Niclas; Haller, Julian; Prediger, Andreas (Frontiers in Bioengineering and Biotechnology, 2025)
The increased application of single-use (SU) equipment and sensor technology in biopharma and bioprocesses has a significant impact on development and production. User are faced with the question how sensor uncertainties of SU devices can be handled and estimated to ensure process reliability. The classical methods by means of calibration and resulting uncertainty determination are only transferable to SU sensors to a limited extent. Sensor elements are often delivered pre-assembled and without the possibility of in-process calibrations. Moreover, manufacturers’ specifications do not use strictly defined terms but constructions such as “1-sigma accuracy”, which makes it even more difficult for the end customer to determine sensor uncertainties. The purpose of this article is to demonstrate the determination of measurement uncertainty using a 1/2-inch BioPAT®Flow SU sensor as an example to accomplish a comparison with the accuracy specification given in the sensor data sheet. A linear regression could be determined as the upper limit of the combined measurement uncertainty: uQ=0.0114 Q+0.182 L/⁡min.